Development of NASICON-type glass ceramic membranes for rechargeable Li-ion/air batteries - Zhang, Yueqi. (2012)
Rechargeable solid-state batteries have gained immense interest in recent years due to safety concerns in the development of lithium ion technology, which utilizes flammable organic liquid electrolytes. Glass ceramics have been studied extensively as solid electrolytes, due to their high lithium ion conductivity in the range of 10-3-10-4 S cm-1, also known as superionic or fast ion conductors. This work aims to achieve thin (~0.3mm), water-stable Li+ ion conductive solid glass ceramic lithium aluminum germanium titanium phosphate (LAGTP) electrolytes, Li1.4Al0.4(Ge2−xTix)1.6(PO4)3 (LAGTP), with NASICON structure. The glass ceramics are developed by glass melting and quenching methods. Field emission scanning electron microscope (FE-SEM) imaging, X-Ray diffraction (XRD), Raman micro-scattering and Electrochemical Impedance Spectroscopy (EIS) are employed to show the effect of sintering temperature on conductivity while generating secondary crystalline phases. Furthermore, quartz, which serves as a strengthening material, is added to LAGTP electrolytes and similar tests are conducted. Solid glass ceramic electrolytes with sufficient mechanical properties can inhibit lithium anode roughening, formation and growth of dendrites in rechargeable lithium batteries.